Secondary symbionts affect aphid fitness and the titer of primary symbiont - Liu, Shen; Liu, Xiaobei; Zhang, Tiantao; Bai, Shuxiong; He, Kanglai; Zhang, Yongjun; Francis, Frédéric; Wang, Zhenying (Frontiers in Plant Science, 2023)
Bacterial symbionts associated with aphids are important for their ecological fitness. The corn leaf aphid, Rhopalosiphum maidis (Fitch), is one of the most damaging aphid pests on maize and has been reported to harbor Hamiltonella defensa and Regiella insecticola while the effects of the secondary symbionts (S-symbionts) on host ecology and primary symbiont Buchnera aphidicola remain unclear. Here, four aphid strains were established, two of which were collected from Langfang - Hebei Province, China, with similar symbiont pattern except for the presence of H. defensa. Two other aphid strains were collected from Nanning - Guangxi Province, China, with the same symbiont infection except for the presence of R. insecticola. Phylogenetic analysis and aphid genotyping indicated that the S-symbiont-infected and free aphid strains from the same location had identical genetic backgrounds. Aphid fitness measurement showed that aphid strain infected with H. defensa performed shortened developmental duration for 1st instar and total nymph stages, reduced aphid survival rate, offspring, and longevity. While the developmental duration of H-infected strains was accelerated, and the adult weight was significantly higher compared to the H-free strain. Infection with R. insecticola did not affect the aphid’s entire nymph stage duration and survival rate. As the H-strain does, aphids infected with R. insecticola also underwent a drop in offspring, along with marginally lower longevity. Unlike the H-infected strain, the R-infected strain performed delayed developmental duration and lower adult weight. The B. aphidicola titers of the H-infected strains showed a steep drop during the aphid 1st to 3rd instar stages, while the augmentation of B. aphidicola titers was found in the R-infected strain during the aphid 1st to 3rd instar. Our study investigated for the first time the effect of the S-symbionts on the ecology fitness and primary symbiont in R. maidis, indicating that infection with secondary symbionts leads to the modulation of aphid primary symbiont abundance, together inducing significant fitness costs on aphids with further impact on environmental adaptation and trophic interactions.